An improved TOPSIS-based multi-criteria decision-making approach for evaluating the working condition of the aluminum reduction cell. (January 2023) - Huang, Zhaoke; Yang, Chunhua; Zhou, Xiaojun; Gui, Weihua
Abstract: The working condition evaluation of the aluminum reduction cell is the basis of formulating operation strategy, ensuring production safety and realizing stable and optimized operation of the aluminum electrolysis process. In this study, we deal with the cell working condition evaluation problem from a new perspective, and an improved Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) based multi-criteria decision-making approach is proposed. This approach starts from the process data and working condition standard. In order to obtain the appropriate weights to the process indicators, Criteria Importance Through Inter-criteria Correlation (CRITIC) approach is used in the proposed approach. Then the TOPSIS is used to calculate the relative closeness of the cell working condition to the working condition standard. Finally, a crisp level determination approach is used to provide a delicate level associated with the working condition standard. Two real cases demonstrated that the proposed approach is useful and effective in the working condition evaluation of the aluminum reduction cell.